Using of the Geophysical Methods to Detect Submerged Targets and their Impact on the Sedimentary and Morphological Situation in Shatt Al-Arab River/ Basrah, Southern Iraq - Al-Zubaidi, Ahmed A.; Al-Mosawi, Walaa M.; Kadhim, Hamzah A.; Fakher, Ahmed J. (Mesopotamian Journal of Marine Sciences, 2025)
Shatt Al-Arab River in Basrah Governorate is one of the most important rivers and waterways in southern Iraq. It consists of the confluence of the Tigris and Euphrates rivers in Qurna city, north of Basrah Governorate. The river has been subjected to environmental degradation due to many human effects. The most important of these effects is the presence of many wrecks and debris visible and completely submerged. The present study used Side Scan Sonar (SSS) and Sub Bottom Profiler (SBP) techniques to identify the submerged wrecks and detect the impact of these wrecks on the sedimentary situation of the river. The SSS and SBP surveys revealed the presence of 66 distinctive sites for these targets, in addition to different targets have been recorded mostly represented debris and a lot of tires. Some sites contained more than wrecks, as some sites recorded the presence of more than 5 wrecks. The targets identified include medium and small boats, tankers, pontoons, bridge structures, tugs, and unknown debris. Many completely submerged debris and shipwrecks have been discovered in the river. The SBP sections and satellite images explained that the presence of many wrecks, especially the large sizes, significantly changed the shape of the river banks over many years through their trapping of sediments